Persepsi orang tua mengenai pengenalan bahasa inggris pada anak usia dini di Desa Baru Kecamatan Batang Kuis - Ani Deswita Chaniago; Utary Dwi Listiarini; Linda Hernike Napitupulu; Syafrizaldi Syafrizaldi (Journal of Pharmaceutical and Sciences, 2023)
Introduction : The focus of this research is to find out how parents see the importance of learning English for young children. Methods: This research is a qualitative type using a descriptive approach through focus group discussions (FGD) and was carried out naturally in Baru Village, Batang Kuis District, North Sumatra. Results: The results showed that out of 15 respondents, most parents believed that 80% was important for young children to learn English, while some did not know that foreign languages could be taught from an early age. In addition, 20% more learning English at an early age improves children's memory and brain formation, and children will have greater curiosity if taught English. Conclusion: Most of the respondents have a good perception and strongly agree for the introduction of English in early childhood considering that English is very important at this time.